Eight Cousins; Or, The Aunt-Hill - Alcott, Louisa May, 1832-1888 (Salt Lake City, UT : Project Gutenberg, 2012)
"Eight Cousins; Or, The Aunt-Hill" by Louisa May Alcott is a novel published in 1875. Thirteen-year-old orphan Rose Campbell arrives at her wealthy family's estate, sickly and uncertain of her future. When her unconventional guardian Uncle Alec returns from abroad, he revolutionizes her care with unorthodox ideas about health and education. Surrounded by seven boisterous boy cousins and befriending the housemaid Phebe, Rose must navigate family dynamics while discovering who she wants to become in this exploration of childhood, education, and finding one's place. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Eight_Cousins
Release date is 2012-01-13
E-text prepared by Suzanne Shell, Emmy, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Orphans -- Juvenile fiction; Cousins -- Juvenile fiction; Family life -- Juvenile fiction